Functional impact of biological rhythm disturbance in bipolar disorder - Giglio, Larriany M.; Magalhães, Pedro V.S.; Kapczinski, Natalia S.; Walz, Júlio C.; Kapczinski, Flávio (Journal of psychiatric research, 2010)
Bipolar disorder (BD) is characterized by frequent recurrence, incomplete recovery, cognitive dysfunction and poor functioning. Impairment lingers in the interepisodic period and mechanisms leading to this dysfunctional state are not fully comprehended. To our knowledge the association of biological rhythm dysfunction with functioning in BD has not been assessed directly. The objective of this study was to measure and quantify the impact of rhythm dysfunction on interepisodic functioning in BD. We also tested the association between executive functioning and sleep and rhythm problems. Eighty-one outpatients with BD and 79 matched control subjects were consecutively recruited. Functional impairment was assessed with the Functioning Assessment Short Test (FAST) and biological rhythms with the Biological Rhythms Interview of Assessment in Neuropsychiatry (BRIAN). A subsample had their executive functioning assessed with the Wisconsin Card Sorting Test (WCST). Patients and control subjects were well matched. Functioning and rhythm scores were correlated in patients and control subjects. The BRIAN score was the strongest predictor of functioning in the regression model. Biological rhythms partially mediated the impairment associated with bipolar disorder. The rhythm score was also associated with executive functioning. Biological rhythm dysfunction was a potent predictor of functioning in interepisodic patients with bipolar disorder; it may also mediate much of the disorder-induced disability. These results further the notion that biological rhythms may be interesting targets for diverse interventions aiming to improve functioning and prevent relapse in interepisodic bipolar disorder.